2003
DOI: 10.1034/j.1399-3062.2003.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of herpes virus infections in renal transplant recipients exposed to high mycophenolic acid plasma concentrations

Abstract: Viral infections constitute an important problem for transplant recipients and their physicians. Often the balance between adequate and over-immunosuppression is hard to find and therapeutic drug monitoring might be a welcome adjunct in the management of transplant patients. We report four renal transplant recipients with extra-ordinary presentations of viral disease who were all treated with mycophenolate mofetil and in whom high mycophenolic acid (MPA) trough levels were found. High MPA levels may reflect ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…1 Since infection may be allograft or life threatening it is managed with a high index of suspicion and an arsenal of prophylaxis, pre-emptive and therapeutic treatment. 2 A number of the infections characteristic of immunosuppression have typical ocular manifestations.…”
mentioning
confidence: 99%
“…1 Since infection may be allograft or life threatening it is managed with a high index of suspicion and an arsenal of prophylaxis, pre-emptive and therapeutic treatment. 2 A number of the infections characteristic of immunosuppression have typical ocular manifestations.…”
mentioning
confidence: 99%
“…One of the components of this immunosuppressive scheme is MMF, which specifically inhibits B‐lymphocyte and T‐lymphocyte proliferation (12). Reports suggest an increased incidence in severe and unusual manifestations of herpesvirus infections since introduction of MMF (13–15). It has been suggested that high mycophenolic acid (MPA) trough levels are associated with viral infections (15).…”
Section: Discussionmentioning
confidence: 99%
“…levels are associated with an increased frequency of rejection (20), whereas elevated MPA trough levels are related to an increased risk for infections (21). Nevertheless, relevant correlations between MPA trough levels and MPA-AUC values could not be detected, therefore the usefulness of measuring trough levels in routine care of renal transplant recipients is doubted (22)(23)(24).…”
mentioning
confidence: 99%